Pengelolaan Kesejahteraan Karyawan di Perusahaan Multinasional di Indonesia: Antara Harapan dan Realitas - Juharudin, Uding; Perkasa, Didin Hikmah (Innovative: Journal Of Social Science Research, 2024)
Employee welfare management is an important aspect in maintaining productivity and job satisfaction, especially in multinational companies operating in Indonesia. This study aims to analyze employee welfare management in multinational companies with a focus on the gap between employee expectations and reality. Using a literature review method, this study examines various literature and previous studies related to welfare policies, such as wages, benefits, working conditions, and health and safety programs. The results of the study indicate that although many multinational companies in Indonesia are committed to providing optimal welfare for employees, there are significant challenges in its implementation, including differences in work culture, diverse regulations, and gaps between parent company and subsidiary standards in Indonesia. This reality often creates employee dissatisfaction, which can affect turnover and decreased performance. This study recommends that multinational companies adjust welfare policies that are more contextual to local needs, and conduct ongoing evaluations to bridge the expectations and realities of employee welfare in Indonesia.